IW-Weiterbildungserhebung 2023: Investitionsvolumen auf Höchststand; IW further training survey 2023: Investment volume at an all-time high - Susanne Seyda; Sabine Köhne-Finster; Fritz Orange; Thomas Schleiermacher (IW-Trends - Vierteljahresschrift zur empirischen Wirtschaftsforschung, 2024)
Die Weiterbildungsaktivität erreichte im Jahr 2022 laut IW-Weiterbildungserhebung, an der sich 953 Unternehmen beteiligten, einen Höchststand: 93 Prozent der Unternehmen bieten ihren Mitarbeitern Weiterbildung an. Jeder Beschäftigte investierte durchschnittlich 20,3 Stunden - ein Plus von zwei Stunden oder rund 10 Prozent gegenüber 2019. Die Investitionen in Weiterbildung betrugen im Durchschnitt 1.347 Euro pro Mitarbeiter. Insgesamt investierte die Wirtschaft 46,4 Milliarden Euro in Weiterbildung und damit real 2,3 Prozent mehr als 2019. Über 90 Prozent der Unternehmen bieten informelle und non-formale Weiterbildungen an. Mehr als ein Drittel ermöglicht den Erwerb formaler Abschlüsse durch betriebliche Weiterbildung, zum Beispiel Aufstiegsfortbildungen oder Teilqualifikationen. Die Nutzung digitaler Lernangebote ist mittlerweile fest etabliert. Besonders beliebt ist dabei das interaktive webbasierte Lernen. Die meisten Weiterbildungen vermitteln inhaltlich berufliches Fachwissen, IT-Anwendungs- und Branchenkenntnisse. Soziale Kompetenzen, Führungskompetenzen und Nachhaltigkeit werden hingegen seltener behandelt. Größtes Hemmnis der Weiterbildung ist Zeitmangel. Trotz zahlreicher Herausforderungen durch die Transformation sieht ein Teil der Unternehmen keinen weiteren Weiterbildungsbedarf oder bemängelt ein zu geringes Interesse der Beschäftigten. Hier könnten neben einer finanziellen Förderung individuell zugeschnittene Weiterbildungsangebote und die Möglichkeit, von anderen Unternehmen zu lernen, sinnvoll unterstützen. – – In 2022 further training activity in German industry reached an all-time high. As the results of a survey of almost pri1,000 companies conducted as part of the 2023 IW Further Training Survey show, 93 per cent of enterprises offer their employees further training. In the period covered by the survey, every worker invested an average of 20.3 hours - an increase of two hours or around 10 per cent over 2019. Investment in further training increased by 9 per cent in nominal terms to an average of exteuro1,347 per employee. Overall, investment in further training by businesses totalled 46.4 billion euros - another new record. Over 90 per cent of companies offer informal and non-formal further training. More than a third of firms enable their workforce to obtain formal qualifications building on their original vocational training. These might be courses leading to positions of greater responsibility or covering particular aspects of their work. Boosted dramatically by the Covid19 pandemic, the use of digital learning is now firmly established, and interactive web-based courses are particularly popular. Most further training advances participants' skills in their existing professions, but many firms also offer training in IT applications and other subjects relevant to their sector. Social and leadership skills and issues around sustainability are covered less frequently. The greatest obstacle to participation in further training is employees' lack of time. Despite the numerous challenges posed by the transformation, some companies see no need for further training or criticise the lack of interest among their staff. In addition to financial support, individually tailored further training programmes and the opportunity to learn from other companies might usefully combat this resistance. As companies face the challenge of transformation, better internal communication highlighting the importance of further training would also be helpful.
Keywords: I22; J24; M53; 330; betriebliche Weiterbildung; Unternehmensbefragung; digitale Lernangebote